2019
DOI: 10.1016/j.isci.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Association of Halogen Bonding and Hydrogen Bonding in Metal Acetate-Catalyzed Asymmetric Halolactonization

Abstract: SummaryCooperative activation using halogen bonding and hydrogen bonding works in metal-catalyzed asymmetric halolactonization. The Zn3(OAc)4-3,3′-bis(aminoimino)binaphthoxide (tri-Zn) complex catalyzes both asymmetric iodolactonization and bromolactonization. Carboxylic acid substrates are converted to zinc carboxylates on the tri-Zn complex, and the N-halosuccinimide (N-bromosuccinimide [NBS] or N-iodosuccinimide [NIS]) is activated by hydrogen bonding with the diamine unit of chiral ligand. Halolactonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…[3] Theh ighly directional and soft character of XB complexes have been applied in crystal engineering, [4] biomolecular systems, [5] and catalysis. [6][7][8] In 2008, Bolm et al reported XB-donor-catalyzed reduction of quinolines by Hantzsch esters. [7a] After this seminal work, other catalytic reactions were successfully developed for the activation of lone-pair-possessing heteroatoms (Y) in the substrates (e.g., imine derivatives, [7a,e,h,o,q,r] carbonyl compounds, [7c,f,j,l,m,n,r] alkyl halides, [7d,g] thioamides, [7i] iodonium ylides, [7k] and N-haloamides [7p] ;F igure 1B,l eft).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Theh ighly directional and soft character of XB complexes have been applied in crystal engineering, [4] biomolecular systems, [5] and catalysis. [6][7][8] In 2008, Bolm et al reported XB-donor-catalyzed reduction of quinolines by Hantzsch esters. [7a] After this seminal work, other catalytic reactions were successfully developed for the activation of lone-pair-possessing heteroatoms (Y) in the substrates (e.g., imine derivatives, [7a,e,h,o,q,r] carbonyl compounds, [7c,f,j,l,m,n,r] alkyl halides, [7d,g] thioamides, [7i] iodonium ylides, [7k] and N-haloamides [7p] ;F igure 1B,l eft).…”
mentioning
confidence: 99%
“…[14] Among the azolium salts tested, the 2-iodoimidazolinium salt 1d promoted the reaction most efficiently,r esulting in 81 %y ield of the product (entry 4). TheN H-free indoles,w hich have substituents at the 5-position, were also suitable for the reaction, resulting in good yields of products (entries [5][6][7][8]. Chloroform was the best solvent choice (entry 10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bromolactonization products 3 could be transformed to other chiral heterocyclic compounds. For example, product 3 a was readily converted to gem ‐disubstituted epoxide 10 possessing a quaternary carbon center without loss of the stereo‐information (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…Electrostatic noncovalent interactions between the σ‐hole of electron‐deficient halogen atoms (e.g., C−X, X=I, Br, Cl; XB donor) and a Lewis base (XB acceptor) can form XB complexes (Figure B) . The highly directional and soft character of XB complexes have been applied in crystal engineering, biomolecular systems, and catalysis . In 2008, Bolm et al.…”
Section: Figurementioning
confidence: 99%